Do NSAID/COX-2 Inhibitors Increase Nonunion After Fracture Surgery? Dilemma and Consideration In Use - Azmi (Universitas Airlangga, 2022)
Background: Nonunion accounts for 2% to 10% of fracture complications, diminishing quality of life and increasing mortality risk. Several factors, including smoking, metabolic disorders, dietary inadequacy, and nonsteroidal anti-inflammatory drugs (NSAIDs), may predict nonunion development. NSAIDs are frequently used to treat postoperative pain, including in orthopedic conditions, particularly for fracture pain management. However, NSAID/cyclooxygenase (COX)-2 inhibitor use has been controversial for many years. Many orthopedic surgeons avoid using them in fracture surgery due to their potential adverse effects on osteogenesis and subsequent nonunion risk.Literature Review: An updated literature review was conducted using digital databases such as PubMed, Cochrane, Ovid-SP, Springer Link, and Science Direct, with the search terms